2014
DOI: 10.1016/j.cpr.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Can mindfulness and acceptance be learnt by self-help?: A systematic review and meta-analysis of mindfulness and acceptance-based self-help interventions

Abstract: Recommendations for research and practice are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
223
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(248 citation statements)
references
References 63 publications
22
223
1
2
Order By: Relevance
“…Spijkerman et al (2016), however, were unable to conduct subgroup analyses based on studies' type of comparison condition. Similarly, a systematic review by Cavanagh et al (2014) found that mindfulness-and acceptance-based self-help interventions had small statistically significant benefits on anxiety and depression outcomes relative to comparison conditions. Although Cavanagh et al (2014) included trials of books/workbooks, audio recordings, and Internet-delivered interventions, four of which are featured in this review, the current findings support and expand upon their conclusion that contextual or third-wave treatments can be delivered efficaciously in various formats.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Spijkerman et al (2016), however, were unable to conduct subgroup analyses based on studies' type of comparison condition. Similarly, a systematic review by Cavanagh et al (2014) found that mindfulness-and acceptance-based self-help interventions had small statistically significant benefits on anxiety and depression outcomes relative to comparison conditions. Although Cavanagh et al (2014) included trials of books/workbooks, audio recordings, and Internet-delivered interventions, four of which are featured in this review, the current findings support and expand upon their conclusion that contextual or third-wave treatments can be delivered efficaciously in various formats.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, a systematic review by Cavanagh et al (2014) found that mindfulness-and acceptance-based self-help interventions had small statistically significant benefits on anxiety and depression outcomes relative to comparison conditions. Although Cavanagh et al (2014) included trials of books/workbooks, audio recordings, and Internet-delivered interventions, four of which are featured in this review, the current findings support and expand upon their conclusion that contextual or third-wave treatments can be delivered efficaciously in various formats. Conversely, the estimated effects of third-wave eHealth treatments in the current review are lower than those of third-wave therapies delivered in individual and group face-to-face format (Öst, 2008).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations